Multi Tier Architecture Model On A Server Cluster For Application Of Big Data - Zaid Amin; RM Nasrul Halim (Annual Research Seminar (ARS), 2017)
This research focused on the development ofscientific contributions in the field of network computer, wherethe results of this research is solutions for developers orpractitioner in determining the model topology and routingconfiguration protocols to suit the needs of the application for bigdata. Term goals this research such as sustainable road map thatare able to produce robustness and reliability networks forapplication of big data. The methods that Researchers use on thisresearch is PPDIOO (Prepare, plan, design, implementation,operate, and optimize). Researchers limiting stages the use of themethods of development of the network until the stage of thedesign with the results in the form of the simulation and design ofnetwork topology, especially on a business organization orgovernment.